Corrosion Mechanism Study on Welded Austenitic Stainless Steel - Ahmad Rahim, Farhana Aqilah (2018)
Austenitic stainless steels 304 are important material that have variety application such as marine, construction, oil and gas exploitation, chemical industries, and ship building. However, welding process on austenitic stainless-steel change the stability of passive film on surface stainless steel causes corrosion attack when exposed to the chloride environment. It is found that domestic storage water heater end user encounter premature corrosion and leakage in heater shells. This study focuses on the effect of temperature on the corrosion behavior of welded austenitic stainless steel 304. A corrosion immersion test was employed to get the corrosion rate of the welded austenitic stainless steel 304. Corrosion immersion test was following standard ASTM G48 Ferric Chloride Pitting Test. The welded part of specimens was prepared by using gas tungsten arc welding (GTAW). Temperature of ferric chloride solution are the parameters that involve in determining corrosivity of welded austenitic stainless steel 304. Ferric chloride pitting test results showed that pitting corrosion on welded part of austenitic stainless steel are more severe in high temperature (60°C) than in low temperature (15°C). Furthermore, hardness test of welded part of austenitic stainless steel 304 decreases when tested in high temperature (60°C). Visual inspection and scanning electron microscope were used to examine the corrosion microstructure and morphology features of the specimens before and after corrosion attacked.